Dose-dependent effects of aqueous Xylopia aethiopica fruits extract on uterine apoptotic markers and placental histology in pregnant Wistar rats (Health and Biosciences, 2026)
Apoptosis plays a critical role in uterine remodeling and placental development during pregnancy, with caspase-3 and caspase-8 serving as key regulatory enzymes. Xylopia aethiopica fruit (Ethiopian pepper) is widely used in African ethnomedicine, including during pregnancy, yet its effects on apoptotic pathways in gestation remain insufficiently characterized. This study investigated the effect of aqueous extract of Xylopia aethiopica fruit on uterine caspase-3 and caspase-8 levels and placental histology in pregnant Wistar rats during mid-gestation. Sixteen pregnant Wistar rats (150–180 g) were assigned into four groups (n = 4): control and extract-treated groups receiving 250, 500, or 1000 mg/kg body weight orally once daily from gestational days 8–14. Uterine tissues were analyzed for caspase-3 and caspase-8 levels using ELISA, while placental tissues were examined histologically using hematoxylin and eosin staining. Data were analyzed using one-way ANOVA with Bonferroni post hoc test at p < 0.05. The aqueous extract of Xylopia aethiopica produced a dose-dependent reduction in uterine caspase-3 and caspase-8 levels. Significant decreases were observed at 500 mg/kg and were more pronounced at 1000 mg/kg compared with the control group. Histological findings revealed preserved placental architecture in the control and low-dose groups, while moderate and high doses induced degeneration and necrosis of glycogen-rich cells within the labyrinth and junctional zones. Xylopia aethiopica aqueous extract modulates apoptotic activity in uterine tissues during mid-pregnancy in a dose-dependent manner. While low doses appear relatively safe, higher doses compromise placental integrity, indicating a narrow margin between therapeutic and toxic effects during pregnancy.